Python Language Teaching Evaluation System Based on LLM large model - Yang, Haotian (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of information technology and artificial intelligence, programming education is very important. However, the traditional Python language teaching evaluation method has some problems, such as strong subjectivity and low efficiency, which is difficult to meet the current situation of contemporary programming education. In order to overcome the limitations of traditional teaching methods and comprehensively evaluate students ’programming ability, the system uses LLM model to analyze code, and combines with the Streamlit framework to build a user interface to achieve convenient interaction and feedback. The experimental results show that the system has high accuracy and reliability, which can effectively evaluate students ’programming level and provide support for personalized teaching. Then it can promote the development of programming education